A geometric approach to cosmological boundary conditions - Savi, L. L [UNESP] (2015)
The observed T-asymmetry of macroscopic physics is traced back to the extremely low entropy conﬁguration of the early universe. Although matter was very hot and with a uniform temperature at that stage, the gravitational degrees of freedom were largely suppressed, which fact contributes to the lowness of the entropy and is encoded in the high level of spatial symmetry (nearly Friedman-Lemître-Robertson-Walker character) of the last scattering surface. I analyze diﬀerent attempts to explain the origin of such special conﬁguration. The inﬂation paradigm is probed with respect to this problem, and it is concluded that the initial low entropy cannot be accounted for within it. Similar conclusions are reached with respect to statistical (i.e. anthropic) reasonings. On the other hand, the paradigm known as conformal cyclic cosmology (CCC) presents itself as a new alternative which surpasses many of the diﬃculties faced by its rivals, although raising its own open questions. I introduce the model together with the mathematical structure of Cartan geometries as a possible means of achieving a better understanding of cosmological boundary conditions. One element which is crucial in this analysis is the modeling of the Cartan geometric structure over a de Sitter space SOe(4,1)/SOe(3,1) with varying length parameter. The introduction of a length parameter in the kinematics is favored by the observation of a positive cosmological constant and also desirable for quantum gravity reasons, due to the natural scale set by Planck's constant